A study of factors influencing endemic stability and instabiity to theileriosis and babesiosis on dairy production in Muranga district, Kenya. - Gitau, G.K. (University of Nairobi, 1997)
This thesis describes a study of the epidemiology of theileriosis on smallholder dairy farms in Murang'a District situated in central highlands of Kenya. The main objectives were: 1) to characterise different areas within the district as to their risks for tick-borne diseases (TBDs), in particular infection due to Theileria parva, and to classify the potential endemically stable and unstable areas. 2) Estimate health and productivity parameters such as infection rates, morbidity and mortality rates, dynamics of infection and growth patterns in contrasting grazing systems and agro-ecological zones (AEZs) in Murang'a District, Kenya. 3) To study the potential risk factors associated with T parva infections in cattle in smallholder dairy farms in Murang'a District of Kenya. The study was conducted in two phases. The first phase was a cross-sectional study to estimate the prevalence to tick-borne infections and was conducted between March and June 1994. The cross-sectional serological study was carried out on 750 smallholder dairy farms in Murang'a District, selected in a stratified random sampling method. One hundred and fifty farms were studied from three administrative sub locations in each of the five AEZs. These five AEZS were: Lower Highlands 1 (LH 1), (tea-dairy; altitude, 1730-2130m; mean annual temperature, 15-18°C; annual rainfall, 1700-240Omm); Upper Midlands 1 (UM 1), (coffee-tea; altitude, 1670-180Om; mean annual temperature, 18.0-18.8°C; annual rainfall, 1700-190Omm); UM 2 (main coffee; altitude, 1500-167Om; mean annual temperature, 18.8-19.7°C; annual rainfall, 1300-162Omm); UM 3 (marginal coffee; altitude, 1340-150Om; mean annual temperature, 19.7-20.7°C; annual rainfall, 900- 135Omm); and UM 4 (sunflower-maize; altitude, 1340-152Om; mean annual temperature, 19.5-20.7°C; annual rainfall, 850-95Omm). The farms had a total of362 calves (148 males and 214 females) aged between 6-18 months. Prevalence of serum antibodies to three tick-borne parasites, that is T parva, T mutans and Babesia bigemina, were determined using the Enzyme-Linked Immunosorbent Assay (ELISA) technique. Antibody prevalence values significantly differed across the AEZs. The ranges of means for the antibody prevalence were: T parva (18-72%), T mutans (1.5-28%) and B. bigemina (12-49%). There were significant differences in serum antibody prevalence for the different TBD parasites across the fives AEZs (p<O.05). The factors that were significantly associated with variations in antibody prevalence are described below. For T parva, Zebu breeds and their crosses with Taurine breeds were significantly (p<O.05) associated with higher prevalences than Taurine breeds. Higher prevalence was significantly (p<O.05) associated with calves on open grazing than those on zero-grazing. For T mutans, Zebu calves and their crosses with Taurine breeds had significantly (p<O.05) higher antibody prevalence than Taurine breeds. For B. bigemina, LH 1 and UM 1 were significantly (p<O.05) associated with higher prevalence than the other three AEZs. Higher prevalences were also significantly (p<O.05) associated with calves grazed freely, when compared to those partially or completely confined. Significantly (p<O.05)higher prevalences were seen in older calves and male calves than in younger and female calves. Calves that reportedly had never received any acaricide treatment had significantly (p<O.05) higher prevalence than those that had received acaricide treatment, regardless of the method used. The above results served as indicators of possible existence of endemic stability in some AEZs for some parasites. The second phase was a longitudinal (prospective) study to estimate incidences of T parva infections, such as sero-conversion to T parva and calf morbidity, as well as calf mortality and growth rates associated with different AEZs and grazing systems. The longitudinal study was conducted over a period of one-and-a-halfyears between March 1995 and August 1996 in three agroecological zones (AEZs) namely, Upper Midlands 1,2 and 4, (UM 1,UM 2 and UM 4). The three AEZs were selected based on the serum antibody prevalence results from the cross-sectional study shown below. Two of the AEZs studied were identified as having highest (UM 4 - above 70%) and lowest risk (UM 1 - below 40%) of T parva infections and for morbidity and mortality to ECF while the third (UM 2) was an intermediate zone. Study farms were also stratified by grazing pattern (restricted versus unrestricted) for the high and low risk areas. A total of 188 smallholder dairy farms were selected purposively from which a total of 225 female calves were recruited (also purposively) and were visited within the first two weeks of life and thereafter at biweekly intervals up to the age of 6 months. The mean number of cattle in these smallholder farms was 2.6. The 225 female calves were distributed as follows: 76 in UM 1, 50 in OM 2 and 99 in UM 4. In UM 1, 35 and 41 calves were from farms which practised restricted and unrestricted grazing respectively. In UM 4, 51 and 48 calves were from farms . which practised restricted and unrestricted grazing respectively. Both exotic and indigenous breeds of cattle and their crosses were present, with the former predominating. All farms in UM 2 (the intermediate zone) practised zero (restricted) grazing. The crude ECF-morbidity rates were: 20.7%, and 33.0%, while ECF-fatality rates were: 8.3%, and 13.2% in UM 1 and UM 4 (low and high risk) respectively. When further stratified by grazing management, zero-grazing farms had lower ECF morbidity rates than open-grazing farms, 2.9% versus 18.4% in UM 1 and 1l.1 % versus 24.7% in open and zerograzing farms in UM 4 and ECF-mortality, 0% versus 8.3% and 2.3% versus 1l.2% in the OM 1 and UM 4 respectively. The risk of exposure to T parva, estimated by determining the incidence of seroconversion was not significantly different across the three AEZs; (35.7%, 39.5 % and 45.4% in UM 1,UM 2 and UM 4 respectively (p>o.05). The factors significantly associated with sero-conversion to T parva in a multi-variate Glimmix model are briefly described below. Zebu breeds and their crosses with exotic breeds were associated with lower risks of seroconversion to T parva than the exotic breeds (p<O.05). Calves whose dam antibodies were high and positive were significantly associated with higher risk of sero-conversion to T parva as were older calves than the young ones (p<O.05). Calves that were reported to have been washed with acaricides to control ticks were associated with higher risks of sero-conversion while calf morbidity was significantly (p<O.05) associated with higher risk of seroconversion. Calves that acquired ECF were associated with significantly (p<O.05) lower sero-conversion risk rates that those which did not sero-convert. The presence of nymphs (total) and nymph (engorged) R. appendiculatus on calves was associated with significantly lower and higher risk of sero-conversion to T parva respectively (p<O.05). Calf mean daily weight gains were mainly associated with calf level factors as described below from a multi-variate mixed model. Older calves were associated with lower mean daily weight gains than young calves, while calves with higher T parva antibody titres were associated with lower mean daily weight gains than those with lower T parva antibody titres (p<O.05). Calves that received concentrate feed supplements were associated with higher mean daily weight gains than those not receiving, while Zebu and their crosses were associated with lower mean weight gains than the Taurine breeds (p<O.05). Calves that experienced any morbidity were associated with lower mean daily weight gains at the time of morbidity than non-affected calves (p<O.05). Calves that experienced ECF -morbidity were associated with higher mean daily weight gains at the time of morbidity than non-affected calves (p<O.05). The presence of female (nonengorged) R. appendiculatus on calves was associated with lower mean daily weight gains in calves (p<O.05).